GEN Z’S PERCEPTION OF GREEN MARKETING THAT SELLS: A CASE STUDY OF #SejauhManaKamuPeduli BY SEJAUH MATA MEMANDANG - Nada Nurkhalisha, Aisya; Surayya Ulfa, Nurist; Luqman, Yanuar (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
The increasing awareness of environmental problems has recently become a concern that has caused many people to take action to use environmentally friendly components. These actions include how companies use green marketing to promote green products. Therefore, the term greenwashing has become more common, raising questions and causing skepticism among consumers. This research aims to examine how skeptical behavior emerges as a response to green marketing that sells in the case of #SejauhManaKamuPeduli by Sejauh Mata Memandang. This research uses the theory of Green Marketing by Hennion & Kinnear, Greenwashing by Jay Westerveld, and Skepticism by Hurtt using qualitative methods and case study Pattern Matching analysis methods, as well as collecting data through interviews with three Gen Z informants. This research shows that skeptical behavior by Gen Z towards green marketing that sells green products begins when someone is exposed to green marketing actions and they’re seeking information about the green product. When information about the green products they are looking for does not meet their expectations, skeptical behavior will emerges.